Bionic lumbar vertebra skeleton with X-ray developing function and preparation method thereof

By using water-based coating process and water-soluble developer KI in medical bone bionic materials, combined with SAN resin emulsion, the problems of insufficient X-ray development performance and biocompatibility are solved, and the development effect is improved and the material hardness is enhanced. It is suitable for Various application scenarios.

CN119185654AActive Publication Date: 2024-12-27QINGDAO UNIV OF SCI & TECH +1
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
CN202411311710.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-20
Publication Date
2024-12-27
Estimated Expiration
2044-09-20

AI Technical Summary

Technical Problem

The development performance of existing medical bone bionic materials under X-ray fluorescence is insufficient, and traditional developer has biocompatibility and environmental friendliness.

Method used

Using the water-based coating process, the water-soluble developer KI and SAN resin emulsion are uniformly mixed through spraying or impregnation to form a bionic lumbar skeleton with X-ray development function, improve development contrast and biocompatibility, and is modified by SAN resin. Enhance mechanical properties.

Benefits of technology

The development effect is significantly improved, environmental protection and biocompatibility are improved, and the material hardness is improved. It is suitable for medical and industrial applications, and customized solutions that meet different needs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119185654A_ABST
    Figure CN119185654A_ABST
Patent Text Reader

Abstract

The invention discloses a bionic lumbar vertebra skeleton with X-ray development and a preparation method thereof, and relates to the technical field of medical polymer material bionics, and the technical scheme is as follows: a rigid polyurethane foam raw material is stirred and mixed and then poured into a lumbar vertebra skeleton mold for foaming to prepare a cancellous bone material of the bionic lumbar vertebra skeleton; the material of the bionic cortical bone is prepared by blending and modifying styrene-acrylic emulsion and SAN emulsion; and attaching the prepared cortical bone to the outer surface of the cancellous bone by adopting a spraying or dipping process to form the bionic lumbar vertebra bone with X-ray development. The water-soluble developing agent is added in emulsion synthesis, so that fine distribution of the developing agent is realized, and the contrast ratio and definition of X-ray development are remarkably improved. Compared with a traditional material depending on a high-concentration inorganic developer, the water-soluble developer has the advantages that the biocompatibility and the environmental protection property are improved, the hardness and the wear resistance of the material are enhanced through the SAN resin, and the water-soluble developer is suitable for diversified medical and industrial application and shows wide market potential.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of bionic medical polymer materials, and in particular to a bionic lumbar vertebra skeleton with an X-ray development function and a preparation method thereof. Background Art

[0002] In recent years, with the progress of materials science and biomedical engineering, the field of medical bone bionic materials has made significant progress. In particular, polymer materials such as polypropylene, polycarbonate, polylactic acid, and polyurethane have become popular research objects for in vivo implantation and in vitro simulation modeling due to their excellent biocompatibility and mechanical properties. These materials can simulate the modulus of real bones, providing new possibilities for 3D printing technology in customized implants and bone repair. However, the ability of these materials to develop under X-ray fluoroscopy is a long-standing technical problem.

[0003] Although medical bone bionic materials have made progress in simulating real bone structures, one of the key problems they encounter in clinical applications is insufficient X-ray fluoroscopy performance. The density of polymer materials is generally lower than that of real bones. For example, the density of materials such as polypropylene is only about 0.9 g / cm 3 , which is much lower than the density of the lumbar vertebrae of young males (about 1.228 g / cm 3 ). This significant density difference leads to high X-ray transmittance, making it difficult to form effective contrast during imaging, which in turn affects the doctor's ability to identify bone structure and lesion details. In addition, existing imaging technologies mainly rely on the addition of inorganic developers, such as barium and iodine, which often need to be used at higher concentrations to achieve ideal imaging effects, but also bring about problems with biocompatibility and environmental friendliness. Therefore, the development of a new type of imaging material that has both good X-ray imaging performance and meets environmental requirements has become a technical problem that urgently needs to be solved.

[0004] The present invention aims to solve the problems of poor development effect and insufficient hardness of bionic bone materials in the prior art. By developing a new type of water-based coating, not only the development effect under X-ray is improved, but also the hardness control can be easily implemented. In addition, while the existing development materials achieve high-contrast development, they often ignore the environmental impact and biocompatibility issues, especially when heavy metals or high-concentration inorganic developers are used. The water-based coating proposed in the present invention adopts an environmentally friendly and odorless formula, and achieves excellent development effect by introducing a water-soluble developer KI, which significantly improves the environmental protection and biocompatibility of the coating. In addition, the colorless and transparent characteristics of the coating and the flexibility of adjusting by adding color provide a wider range of applicability for medical and industrial applications. For example, medical bionic bones can be white, while industrial non-destructive testing can choose eye-catching yellow or blue, thereby meeting a wider range of needs at the technical and application levels. Summary of the invention

[0005] In order to achieve the above-mentioned invention objectives and address the above-mentioned technical problems,

[0006] The present invention provides a bionic lumbar vertebra skeleton with an X-ray development function, wherein the bionic lumbar vertebra skeleton is prepared by the following preparation steps:

[0007] S1 Preparation of cancellous bone material: Mixing hard polyurethane foam raw materials (materials A and B) and pouring them into a lumbar vertebrae bone mold for foaming to prepare a cancellous bone material of bionic lumbar vertebrae;

[0008] Preparation of S2 cortical bone material: The bionic cortical bone material was prepared by blending and modifying styrene acrylic emulsion and SAN emulsion;

[0009] Preparation of S3 bionic lumbar vertebrae skeleton: The prepared cortical bone is then attached to the outer surface of the cancellous bone using a spraying or dipping process to form a bionic lumbar vertebrae skeleton with X-ray imaging.

[0010] Preferably, the specific steps of preparing the cancellous bone are:

[0011] a1 premixing: 100 parts of polyether polyol, 1 part of polydimethylsiloxane (PDMS), 30 parts of 1,4-butanediol, 0.2 parts of catalyst A33, 1 part of triethanolamine, 10 parts of trimethylolpropane, and 0.8 parts of deionized water are stirred evenly in a mixing barrel at a stirring speed of 1000 rpm to obtain material A;

[0012] a2 Add material B and foam: While keeping material A stirring, slowly add 170 parts of polyphenyl polymethylene polyisocyanate (material B), the stirring speed needs to be adjusted to 500 rpm, and stir quickly for 15 seconds;

[0013] a3 Foaming molding: Pour the mixed liquid material quickly into the lumbar vertebrae bone mold and seal the reaction. The temperature inside the mold is controlled at 25°C and the curing time is 24 hours.

[0014] Preferably, the specific steps of preparing the cortical bone are:

[0015] b1 Pre-emulsification of styrene-acrylic emulsion: 10-20 parts of styrene, 20-30 parts of acrylic monomer, 0.5-1.5 parts of emulsifier, 0.1-3.0 parts of chain transfer agent and 10-40 parts of deionized water are mixed in reactor A and stirred to form a pre-emulsion;

[0016] b2 Styrene-acrylic emulsion polymerization: add 10-60 parts of deionized water, 0.5-3 parts of initiator, 0.5-1.0 parts of emulsifier and 1-30 parts of developer into reactor B, stir and heat to 80°C, and dropwise add the pre-emulsion of step a) under nitrogen protection, and carry out emulsion polymerization for 1-2 hours. After the reaction is completed, cool to room temperature to obtain an emulsion;

[0017] b3 Preparation of SAN resin emulsion: 30 parts of styrene (ST), 20 parts of acrylonitrile (AN), 1.0 parts of emulsifier, 0.5 parts of potassium persulfate (KSP), and 100 parts of deionized water were added into reactor C to form styrene-acrylonitrile copolymer (SAN resin) emulsion by emulsion polymerization at a suitable stirring speed;

[0018] b4 Mixed SAN resin modification: The emulsion obtained in step b2 is stirred at a constant temperature in reactor B, 5-40 parts of the SAN resin emulsion prepared in step b3 are slowly added thereto, stirred evenly, the emulsion is cooled to room temperature, 0.1-1.0 parts of pigment are added, and stirred evenly to obtain a SAN resin modified styrene acrylic emulsion with X-ray development function.

[0019] Preferably, the acrylic ester monomer is selected from two or more of ethyl acrylate, butyl acrylate and methyl methacrylate.

[0020] Preferably, the emulsifier is selected from one of sodium dodecylbenzene sulfonate, polyoxyethylene fatty alcohol ether and polyoxyethylene alkylphenol ether, the initiator is ammonium persulfate, and the chain transfer agent is dodecyl mercaptan.

[0021] Preferably, the developer is selected from one or more combinations of potassium iodide KI, sodium iodide NaI, and calcium iodide CaI2.

[0022] Preferably, in step b1, the stirring speed is 1000-2000 rpm, the temperature is controlled at 20-40° C., and the time is 10-20 minutes; in step b2, the stirring speed is 300-500 rpm.

[0023] Preferably, in step b3, the mixing temperature is 40° C., the stirring speed is 1000-2000 rpm, and the time is 10-20 minutes.

[0024] Preferably, in step b4, the constant temperature of reactor B is 40° C., the stirring rate is 300-500 rpm, the SAN resin emulsion is slowly added dropwise over 15 minutes, and the stirring and mixing time after the addition is completed is 30 minutes; after the pigment is added, the stirring rate is 300-500 rpm, and the stirring time is 10 minutes.

[0025] Preferably, the preparation steps in step S3 are:

[0026] The cortical bone material is attached to the surface of the cancellous bone material by spraying or dipping:

[0027] The spraying process is to use a thin spraying process, with a coating thickness of 0.3 mm each time, and the next spraying is carried out after drying, and the number of spraying times is 3-5 times;

[0028] The dipping process is as follows: pour the cortical bone material into a container, immerse all the cancellous bone material in the cortical bone material, slowly pull out of the liquid surface after 30 seconds, and repeat the dipping twice after the emulsion is slowly dried to form a developing coating.

[0029] The technical solution provided by the present invention brings beneficial effects:

[0030] Significant improvement in development effect: The present invention achieves uniform mixing of the developer and the emulsion by adding a water-soluble developer KI during the emulsion synthesis process. This mixing method allows the developer to be distributed in the emulsion in a finer form. Compared with traditional coarse-grained developers, this fine liquid distribution form significantly enhances the contrast and clarity of the development under X-rays. Therefore, a more effective contrast can be formed during the imaging process, significantly improving the doctor's ability to identify bone structure and lesion details, which is crucial for accurate diagnosis and treatment planning.

[0031] Enhanced environmental protection and biocompatibility: Compared with traditional developing materials that rely on high-concentration inorganic developers (such as barium, iodine, etc.), the water-soluble developer KI used in the present invention has obvious advantages in safety and biocompatibility. Low-toxicity water-soluble developers pose less risk to the environment and patient health, and meet the strict requirements of modern medical materials for environmental protection and human safety.

[0032] Improved mechanical properties of coating: The addition of SAN resin in the present invention not only improves the developing properties of the emulsion, but also enhances the mechanical properties of the material by increasing hardness and wear resistance. This makes the modified styrene acrylic emulsion of the present invention particularly suitable for simulating bone materials of people of different ages and different diseases, such as bones of children, adults, the elderly, and osteoporosis patients.

[0033] Wide application and flexibility: In addition to the application of medical bionic bones, the colorless and transparent characteristics of SAN resin modified styrene acrylic emulsion and the adjustable color make it also have a wide range of application potential in the fields of industrial non-destructive testing. Different color options can be adjusted according to specific application requirements, providing more customized solutions.

[0034] In summary, the present invention effectively solves the problem of insufficient performance of medical polymer materials in X-ray development through technical innovation, and improves the biocompatibility and environmental protection of the material by introducing an environmentally friendly water-soluble developer, while enhancing the mechanical properties of the material and broadening its application range. These beneficial effects give the present invention significant advantages and broad market application prospects at the technical and application levels. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 It is the real bone X-ray development effect;

[0036] Figure 2 This is the X-ray development effect of Example 1 of the present invention;

[0037] Figure 3 This is the X-ray development effect of Example 7 of the present invention;

[0038] Figure 4 This is the X-ray development effect of Example 8 of the present invention;

[0039] Figure 5 This is the X-ray development effect of Comparative Example 1 of the present invention;

[0040] Figure 6 This is the X-ray development effect of Comparative Example 3 of the present invention;

[0041] Figure 7 The following are comparison photos of the appearance of the emulsions of Example 1 and Comparative Example 3 of the present invention;

[0042] Figure 8 : These are X-ray development effect diagrams, where a is Example 1, b is real bone, and c is without developer. DETAILED DESCRIPTION

[0043] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. Of course, the specific embodiments described here are only used to explain the present invention and are not used to limit the present invention.

[0044] Example 1

[0045] A bionic lumbar vertebra skeleton with X-ray imaging function is prepared by the following preparation steps:

[0046] S1 bionic lumbar vertebrae cancellous bone preparation:

[0047] a1 premixing: 100 parts of polyether polyol, 1 part of polydimethylsiloxane (PDMS), 30 parts of 1,4-butanediol, 0.2 parts of catalyst A33, 1 part of triethanolamine, 10 parts of trimethylolpropane, and 0.8 parts of deionized water are stirred evenly in a mixing barrel at a stirring speed of 1000 rpm to obtain material A;

[0048] a2 Add material B and mix: While keeping material A stirring, slowly add 170 parts of material B (polyphenyl polymethylene polyisocyanate), the stirring speed needs to be adjusted to 500 rpm, and stir for 15 seconds;

[0049] a3 Foaming molding: Pour the mixed liquid material quickly into the lumbar vertebrae bone mold and seal the reaction. The temperature inside the mold is controlled at 25°C and the curing time is 24 hours.

[0050] Preparation of S2 cortical bone material:

[0051] b1 Pre-emulsification of styrene-acrylic emulsion: 20 parts of styrene, 10 parts of butyl acrylate, 20 parts of methyl methacrylate, 1.0 part of sodium dodecylbenzene sulfonate, 0.3 part of ammonium persulfate and 30 parts of deionized water were mixed in reactor A, and the temperature was raised to 40°C at a stirring speed of 500 rpm. After the temperature stabilized, the stirring speed was adjusted to 2000 rpm and the stirring time was 20 minutes to form a pre-emulsion;

[0052] b2 Styrene-acrylic emulsion polymerization: add 20 parts of deionized water, 0.5 parts of initiator ammonium persulfate, 0.5 parts of emulsifier sodium dodecylbenzene sulfonate and 15 parts of developer KI into reactor B, stir at 400 rpm and heat to 80°C, and add the pre-emulsion of step b1 dropwise under nitrogen protection, and carry out emulsion polymerization for 1 hour. After the reaction is completed, cool to room temperature to obtain an emulsion;

[0053] b3 Preparation of SAN resin emulsion: First, 0.5 parts of potassium persulfate (KSP) was dissolved in 50 parts of deionized water to prepare a 1% KSP aqueous solution for standby use, then 50 parts of deionized water and 1.0 part of sodium dodecylbenzene sulfonate were added to reactor C, and the temperature was raised to 65°C at a stirring speed of 400 rpm. Subsequently, under nitrogen protection, the KSP aqueous solution and the monomer mixture (30 parts of styrene and 20 parts of acrylonitrile premixed) were added dropwise at the same dropping speed. After the addition was completed in 1 hour, the reaction was continued for 1 hour, and finally the temperature was lowered to room temperature while stirring to obtain the SAN resin emulsion;

[0054] b4 Mixed SAN resin modification: The emulsion obtained in step b2 is stirred at a constant temperature in reactor B, 30 parts of the SAN resin emulsion prepared in step b3 are slowly added thereto, stirred evenly, the emulsion is cooled to room temperature, 0.5 parts of pigment are added, and stirred evenly to obtain a SAN resin-modified styrene-acrylic emulsion with X-ray development function.

[0055] S3 bionic lumbar vertebrae cortical bone preparation:

[0056] The cortical bone material prepared in step S2 is coated on the surface of the cancellous bone prepared in step S1 by spraying or dipping:

[0057] The spraying process is to adopt a thin spraying process, the coating thickness of each spraying is 0.3 mm, and the next spraying is carried out after drying, and the number of spraying times is 5 times.

[0058] Example 2

[0059] The same preparation method as in Example 1 was used, except that 5 parts of SAN resin emulsion was added.

[0060] Example 3

[0061] The preparation was carried out in the same manner as in Example 1, except that 10 parts of styrene were added in step b1.

[0062] Example 4

[0063] The preparation was carried out in the same manner as in Example 1, except that polyoxyethylene fatty alcohol ether was selected as the emulsifier.

[0064] Example 5

[0065] The preparation method is the same as that of Example 1, except that polyoxyethylene alkylphenol ether is used as the emulsifier.

[0066] Example 6

[0067] The same preparation method as in Example 1 was used to prepare the product, except that the acrylic acid ester monomers were 10 parts of ethyl acrylate, 10 parts of butyl acrylate and 10 parts of methyl methacrylate.

[0068] Example 7

[0069] The preparation was carried out in the same manner as in Example 1, except that 10 parts of potassium iodide KI and 5 parts of sodium iodide NaI were used as the developer.

[0070] Example 8

[0071] The preparation method is the same as that of Example 1, except that the developer is a combination of 10 parts of potassium iodide KI, 3 parts of sodium iodide NaI and 2 parts of calcium iodide CaI2.

[0072] Example 9

[0073] A bionic lumbar vertebra skeleton with X-ray imaging function is prepared by the following preparation steps:

[0074] S1 bionic lumbar vertebrae cancellous bone preparation:

[0075] a1 Premixing: Mix 10 parts of polyether polyol with 0.5 parts of polydimethylsiloxane (PDMS), 10 parts of 1,4-butanediol, 0.1 parts of catalyst A33, 0.5 parts of triethanolamine, 0.1 parts of trimethylolpropane and 0.1 parts of deionized water in a mixing barrel and stir evenly at a stirring speed of 1000 rpm to obtain material A.

[0076] a2 Add material B and mix: While keeping material A stirring, slowly add 10 parts of material B (polyphenyl polymethylene polyisocyanate), the stirring speed needs to be adjusted to 300 rpm, and stir for 15 seconds.

[0077] a3 Foaming molding: Pour the mixed liquid material quickly into the lumbar vertebrae bone mold and seal the reaction. The temperature inside the mold is controlled at 25°C and the curing time is 24 hours.

[0078] Preparation of S2 cortical bone material:

[0079] b1 Pre-emulsification of styrene acrylic emulsion: In reactor A, 10 parts of styrene, 10 parts of ethyl acrylate, 19 parts of butyl acrylate, 0.5 parts of emulsifier (polyoxyethylene fatty alcohol ether), 0.1 parts of chain transfer agent (dodecyl mercaptan) and 10 parts of deionized water were mixed and stirred to form a pre-emulsion at a stirring speed of 1000 rpm for 10 minutes.

[0080] b2 Styrene-acrylic emulsion polymerization: Add 10 parts of deionized water, 0.5 parts of initiator (ammonium persulfate), 0.5 parts of emulsifier and 1 part of developer (sodium iodide NaI) into reactor B, stir and heat to 80°C, and add the pre-emulsion of step b1 dropwise under nitrogen protection, and carry out emulsion polymerization for 1 hour. After the reaction is completed, cool to room temperature to obtain an emulsion.

[0081] b3 Preparation of SAN resin emulsion: 30 parts of styrene (ST), 20 parts of acrylonitrile (AN), 0.5 parts of polyoxyethylene fatty alcohol ether, 0.5 parts of potassium persulfate (KSP) and 50 parts of deionized water were added into reactor C to form styrene-acrylonitrile copolymer (SAN resin) emulsion by emulsion polymerization method at a suitable stirring speed. The stirring speed was 1000 rpm and the stirring time was 10 minutes.

[0082] b4 Mixed SAN resin modification: The emulsion obtained in step b2 is stirred at a constant temperature in reactor B, 5 parts of the SAN resin emulsion prepared in step b3 are slowly added thereto, stirred evenly, the emulsion is cooled to room temperature, 0.1 parts of pigment are added, and stirred evenly to obtain a SAN resin-modified styrene-acrylic emulsion with X-ray development function.

[0083] S3 bionic lumbar vertebrae cortical bone preparation:

[0084] The dipping process is as follows: pour the cortical bone material into a container, immerse all the cancellous bone material in the cortical bone material, slowly pull out of the liquid surface after 30 seconds, and repeat the dipping twice after the emulsion is slowly dried to form a developing coating.

[0085] Example 10

[0086] A bionic lumbar vertebra skeleton with X-ray imaging function is prepared by the following preparation steps:

[0087] S1 bionic lumbar vertebrae cancellous bone preparation:

[0088] a1 Premixing: Mix 20 parts of polyether polyol with 1.5 parts of polydimethylsiloxane (PDMS), 40 parts of 1,4-butanediol, 0.5 parts of catalyst A33, 1.5 parts of triethanolamine, 10 parts of trimethylolpropane and 3.0 parts of deionized water in a mixing barrel, and stir them evenly at a stirring speed of 2000 rpm for 20 minutes to obtain material A.

[0089] a2 Add material B and mix: While keeping material A stirring, slowly add 170 parts of polyphenyl polymethylene polyisocyanate (material B), the stirring speed needs to be adjusted to 500 rpm, and continue stirring for 15 seconds.

[0090] a3 Foaming molding: Pour the mixed liquid material quickly into the lumbar vertebrae bone mold and seal the reaction. The temperature inside the mold is controlled at 55°C and the curing time is 30 minutes.

[0091] Preparation of S2 cortical bone material:

[0092] b1 Pre-emulsification of styrene acrylic emulsion: 20 parts of styrene, 10 parts of ethyl acrylate, 20 parts of butyl acrylate, 1.5 parts of polyoxyethylene alkylphenol ether, 3.0 parts of chain transfer agent and 40 parts of deionized water were mixed in reactor A and stirred to form a pre-emulsion at a stirring speed of 2000 rpm for 20 minutes.

[0093] b2 Styrene-acrylic emulsion polymerization: Add 60 parts of deionized water, 3 parts of ammonium persulfate, 1.0 part of polyoxyethylene alkylphenol ether and 30 parts of calcium iodide CaI2 into reactor B, stir and heat to 80°C, and add the pre-emulsion of step b1 dropwise under nitrogen protection, and carry out emulsion polymerization for 2 hours. After the reaction is completed, cool to room temperature to obtain an emulsion.

[0094] b3 Preparation of SAN resin emulsion: 30 parts of styrene (ST), 20 parts of acrylonitrile (AN), 1.0 part of polyoxyethylene alkylphenol ether, 0.5 part of potassium persulfate (KSP) and 100 parts of deionized water were added into reactor C, and styrene-acrylonitrile copolymer (SAN resin) emulsion was formed by emulsion polymerization method at a suitable stirring speed. The stirring speed was 2000 rpm and the stirring time was 20 minutes.

[0095] b4 Mixed SAN resin modification: The emulsion obtained in step b2 is stirred at a constant temperature in reactor B, 40 parts of the SAN resin emulsion prepared in step b3 are slowly added thereto, stirred evenly, the emulsion is cooled to room temperature, 1.0 part of pigment is added, and stirred evenly to obtain a SAN resin-modified styrene-acrylic emulsion with X-ray development function.

[0096] S3 bionic lumbar vertebrae cortical bone preparation:

[0097] Dipping process: immerse all the cancellous bone material in the cortical bone material, slowly pull it out of the liquid surface after 30 seconds, and repeat the dipping twice after the emulsion slowly dries to form a developing coating.

[0098] Comparative Example 1

[0099] The same preparation method as in Example 1 was used, except that 5 parts of a conventional developer, barium sulfate, was used as the developer.

[0100] Comparative Example 2

[0101] The same preparation method as in Example 1 was used for preparation, except that no SAN resin emulsion was added for modification. The implementation steps are as follows:

[0102] a) Pre-emulsification: 20 parts of styrene, 10 parts of butyl acrylate, 20 parts of methyl methacrylate, 1.0 part of sodium dodecylbenzene sulfonate, 0.3 part of ammonium persulfate and 30 parts of deionized water were mixed in reactor A, and the temperature was raised to 40° C. at a stirring speed of 500 rpm. After the temperature stabilized, the stirring speed was adjusted to 2000 rpm for 20 minutes to form a pre-emulsion.

[0103] b) Emulsion polymerization: 20 parts of deionized water, 0.5 parts of initiator ammonium persulfate, 0.5 parts of emulsifier sodium dodecylbenzene sulfonate and 15 parts of developer KI were added to reactor B, the temperature was raised to 80°C at a stirring speed of 400 rpm, and the pre-emulsion of step a) was added dropwise under nitrogen protection, and emulsion polymerization was carried out for 1 hour. After the reaction was completed, the stirring speed was adjusted to 300 rpm, the temperature was lowered to 40°C, and 0.5 parts of white pigment (rutile titanium dioxide) was added and the stirring speed was adjusted to 500 rpm. After stirring for 10 minutes, a white styrene-acrylic emulsion with X-ray development function was obtained.

[0104] c) Construction process: Use thin spraying process, the coating thickness of each spraying is 0.3mm, and the next spraying is carried out after drying. The number of spraying times is 5 times.

[0105] Comparative Example 3

[0106] The preparation is carried out in the same manner as in Example 1, except that the process of adding the developer is different. The implementation steps are as follows:

[0107] a) Pre-emulsification: 20 parts of styrene, 10 parts of butyl acrylate, 20 parts of methyl methacrylate, 1.0 part of sodium dodecylbenzene sulfonate, 0.3 part of ammonium persulfate and 30 parts of deionized water were mixed in reactor A, and the temperature was raised to 40° C. at a stirring speed of 500 rpm. After the temperature stabilized, the stirring speed was adjusted to 2000 rpm for 20 minutes to form a pre-emulsion.

[0108] b) Emulsion polymerization: 20 parts of deionized water, 0.5 parts of initiator ammonium persulfate, and 0.5 parts of emulsifier sodium dodecylbenzene sulfonate were added to the reactor B, and the temperature was raised to 80° C. at a stirring speed of 400 rpm, and the pre-emulsion of step a) was added dropwise under nitrogen protection, and the emulsion polymerization was carried out for 1 hour. After the reaction was completed, the stirring speed was adjusted to 300 rpm, and the temperature was lowered to room temperature to obtain an emulsion;

[0109] c) Preparation of SAN resin emulsion: First, 0.5 parts of potassium persulfate (KSP) was dissolved in 50 parts of deionized water to prepare a 1% KSP aqueous solution for standby use, then 50 parts of deionized water and 1.0 part of sodium dodecylbenzene sulfonate were added to reactor C, and the temperature was raised to 65° C. at a stirring speed of 400 rpm. Subsequently, under nitrogen protection, the KSP aqueous solution and a monomer mixture (premixed with 30 parts of styrene and 20 parts of acrylonitrile) were added dropwise at the same dropping speed. After the addition was completed in 1 hour, the reaction was continued for 1 hour, and finally the temperature was lowered to room temperature while stirring to obtain a SAN resin emulsion;

[0110] d) Modification by mixing SAN resin: the emulsion obtained in step b) is heated to 40° C. in reactor B at a stirring rate of 300 rpm, 30 parts of SAN resin emulsion prepared in step c) are slowly added into reactor B within 15 minutes, and stirring and mixing are continued for 30 minutes after the dropwise addition is completed; 15 parts of developer KI and 0.5 parts of white pigment (rutile titanium dioxide) are then added, and the stirring speed is adjusted to 500 rpm. After stirring for 10 minutes, a white SAN resin-modified styrene-acrylic emulsion with X-ray developing function is obtained.

[0111] e) Construction process: Use thin spraying process, the coating thickness of each spraying is 0.3mm, and the next spraying is carried out after drying. The number of spraying times is 5 times.

[0112] Performance Testing

[0113] 1. Hardness test:

[0114] The test of coating hardness is carried out according to the pencil method for measuring paint film hardness standard GB / T 6739-2022. After grinding, cleaning and drying the surface of a tinplate with a size of 120mm×50mm×0.3mm, the prepared emulsion is evenly applied to the surface of the test plate with a paint brush. After drying at room temperature for 7 days, the test is carried out on a pencil scratch hardness tester. The scratch test is carried out three times with a pencil of the same hardness, and the damage of the sample is observed. The hardness of the hardest pencil that does not cause scratches on the coating is used to represent the pencil hardness of the coating.

[0115] 2. X-ray scanning test:

[0116] The Cios Select mobile C-arm X-ray machine of Shanghai Siemens Medical Devices Co., Ltd. was used to test the imaging effect of the prepared bionic lumbar vertebrae under the conditions of 60kV voltage, 10mA current and exposure for 0.2s.

[0117] Table 1 Hardness test data

[0118] sample Pencil hardness Example 1 7H Example 2 4H Example 3 6H Example 6 5H Comparative Example 2 2H

[0119] The hardness in Example 1 is the highest, indicating that the hardness of the coating can be significantly enhanced by using the optimal ratio of SAN resin, which is very critical for the construction of cortical bone in the bionic human bone structure.

[0120] By comparing Example 2 with Example 1, it can be seen that the amount of SAN resin used has a direct effect on hardness. This is because both styrene and acrylonitrile monomers are "hard monomers". Therefore, the hardness of the bionic cortical bone can be regulated by adjusting the amount of SAN resin emulsion to match the modulus of bones in different age groups.

[0121] The data of Examples 3 and 6 further verify the effect of monomer composition on hardness and support the strategy of optimizing hardness by changing the monomer ratio.

[0122] All examples showed higher hardness compared to Comparative Example 2, which emphasizes the innovative use of SAN resin in improving the hardness and overall performance of the coating.

[0123] from Figure 1-6 It can be seen that compared with the real lumbar vertebrae X-ray image ( Figure 1 ) compared with the development effect of adding the traditional developer BaSO4 (Comparative Example 1, Figure 5 ) is poor, because BaSO4 is insoluble in the aqueous phase emulsion, resulting in BaSO4 being dispersed in the emulsion in the form of particles. Its development effect depends on the particle size. The density of BaSO4 is 4.50 g·cm -3 It is very easy to settle and stratify in the emulsion, resulting in poor development effect.

[0124] Comparative Example 3 Figure 6 ) is to add the developer in the reaction step d). At this time, the emulsion system is already stable. Adding potassium iodide or sodium iodide salts will easily cause the emulsion system to break. Figure 7 As shown, the brush coating process also leads to uneven coating film formation due to emulsion demulsification, and gravity causes the developer to easily deposit at the bottom of the bone, resulting in uneven development.

[0125] Figure 7 It is shown that the white emulsion sample of Comparative Example 3 has a stratification phenomenon, with the upper layer being a layer of clear water and the bottom layer being a precipitated emulsion. This stratification is caused by demulsification due to the instability of the emulsion preparation process. Demulsification refers to the aggregation and merging of the dispersed phase (oil droplets wrapped by the emulsifier) ​​in the emulsion due to insufficient stability, and then the separation of the water phase, resulting in the deposition of the emulsion components and the formation of stratification. This phenomenon indicates that the emulsification effect and long-term stability of the emulsion are not good.

[0126] Figure 8 The bionic bone (a) of spraying Example 1, the real vertebra (b), and the bionic bone (c) without spraying the developing coating are compared and developed. It can be seen that (c) has almost no developing effect, while the developing effect of (a) is ideal and close to the developing effect of the real vertebra (b).

[0127] Based on the hardness data and X-ray development effect, it can be concluded that the emulsion has controllable hardness and good X-ray development effect, and can be used as a bone bionic coating. In addition, it can also be used as an industrial X-ray flaw detection coating.

[0128] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A bionic lumbar vertebra skeleton with X-ray imaging function, characterized in that: The bionic lumbar vertebra skeleton is prepared by the following preparation steps: S1 Preparation of cancellous bone material: Mixing hard polyurethane foam raw materials (materials A and B) and pouring them into a lumbar vertebrae bone mold for foaming to prepare a cancellous bone material of bionic lumbar vertebrae; Preparation of S2 cortical bone material: The bionic cortical bone material was prepared by blending and modifying styrene acrylic emulsion and SAN emulsion; Preparation of S3 bionic lumbar vertebrae skeleton: The prepared cortical bone is then attached to the outer surface of the cancellous bone using a spraying or dipping process to form a bionic lumbar vertebrae skeleton with X-ray imaging.

2. The bionic lumbar vertebra skeleton according to claim 1, characterized in that: The specific preparation steps of the cancellous bone are: a1 premixing: 100 parts of polyether polyol, 1 part of polydimethylsiloxane (PDMS), 30 parts of 1,4-butanediol, 0.2 parts of catalyst A33, 1 part of triethanolamine, 10 parts of trimethylolpropane, and 0.8 parts of deionized water are stirred evenly in a mixing barrel at a stirring speed of 1000 rpm to obtain material A; a2 Add material B and foam: While keeping material A stirring, slowly add 170 parts of polyphenyl polymethylene polyisocyanate (material B), the stirring speed needs to be adjusted to 500 rpm, and stir quickly for 15 seconds; a3 Foaming molding: Pour the mixed liquid material quickly into the lumbar vertebrae bone mold and seal the reaction. The temperature inside the mold is controlled at 25°C and the curing time is 24 hours.

3. The bionic lumbar vertebra skeleton according to claim 1, characterized in that: The specific steps of preparing the cortical bone are: b1 Pre-emulsification of styrene-acrylic emulsion: 10-20 parts of styrene, 20-30 parts of acrylic monomer, 0.5-1.5 parts of emulsifier, 0.1-3.0 parts of chain transfer agent and 10-40 parts of deionized water are mixed in reactor A and stirred to form a pre-emulsion; b2 Styrene-acrylic emulsion polymerization: add 10-60 parts of deionized water, 0.5-3 parts of initiator, 0.5-1.0 parts of emulsifier and 1-30 parts of developer into reactor B, stir and heat to 80°C, and dropwise add the pre-emulsion of step b1 under nitrogen protection, and carry out emulsion polymerization for 1-2 hours. After the reaction is completed, cool to room temperature to obtain an emulsion; b3 Preparation of SAN resin emulsion: 30 parts of styrene (ST), 20 parts of acrylonitrile (AN), 1.0 parts of emulsifier, 0.5 parts of potassium persulfate (KSP), and 100 parts of deionized water were added into reactor C to form styrene-acrylonitrile copolymer (SAN resin) emulsion by emulsion polymerization at a suitable stirring speed; b4 Mixed SAN resin modification: The emulsion obtained in step b2 is stirred at a constant temperature in reactor B, 5-40 parts of the SAN resin emulsion prepared in step b3 are slowly added thereto, stirred evenly, the emulsion is cooled to room temperature, 0.1-1.0 parts of pigment are added, and stirred evenly to obtain a SAN resin modified styrene acrylic emulsion with X-ray development function.

4. The bionic lumbar vertebra skeleton according to claim 3, characterized in that: The acrylic acid ester monomer is selected from two or more of ethyl acrylate, butyl acrylate and methyl methacrylate.

5. The bionic lumbar vertebra skeleton according to claim 3, characterized in that: The emulsifier is selected from one of sodium dodecylbenzene sulfonate, polyoxyethylene fatty alcohol ether and polyoxyethylene alkylphenol ether, the initiator is ammonium persulfate, and the chain transfer agent is dodecyl mercaptan.

6. The bionic lumbar vertebra skeleton according to claim 3, characterized in that: The developer is selected from one or more combinations of potassium iodide KI, sodium iodide NaI, and calcium iodide CaI2.

7. The bionic lumbar vertebra skeleton according to claim 3, characterized in that: In the step b1, the stirring speed is 1000-2000 rpm, the temperature is controlled at 20-40° C., and the time is 10-20 minutes; in the step b2, the stirring speed is 300-500 rpm.

8. The bionic lumbar vertebra skeleton according to claim 3, characterized in that: In step b3, the mixing temperature is 40° C., the stirring speed is 1000-2000 rpm, and the time is 10-20 minutes.

9. The bionic lumbar vertebra skeleton according to claim 3, characterized in that: In the step b4, the constant temperature of the reactor B is 40° C., the stirring rate is 300-500 rpm, the SAN resin emulsion is slowly added dropwise for 15 minutes, and the stirring and mixing time after the addition is completed is 30 minutes; after the pigment is added, the stirring rate is 300-500 rpm, and the stirring time is 10 minutes.

10. The bionic lumbar vertebra skeleton according to claim 1, characterized in that: The preparation steps of step S3 are: The cortical bone material is attached to the surface of the cancellous bone material by spraying or dipping: The spraying process is to use a thin spraying process, with a coating thickness of 0.3 mm each time, and the next spraying is carried out after drying, and the number of spraying times is 3-5 times; The dipping process is as follows: pour the cortical bone material into a container, immerse all the cancellous bone material in the cortical bone material, slowly pull out of the liquid surface after 30 seconds, and repeat the dipping twice after the emulsion is completely dry to form a developing coating.

Citation Information

Patent Citations

  • Biodegradable stent and preparation method thereof

    CN105412996A

  • Manufacturing method of human body bionic bone model for medical instrument and equipment developing and practical training

    CN109615994A

  • Polytetrafluoroethylene copolymer emulsion

    CN109771696A

  • Preparation method and application of skeleton-imitating macromolecular composite material for dummy

    CN110982205A

  • Nanometer developer

    CN111534161A